Influence of Fe 3+ ion substitution on structural, magnetic properties and magnetoresistance effect of Pr0.75Na0.05 K0.20MnO3 system / Siti Sumaiyah Sheikh Abdul Aziz ... [et al.] - Sheikh Abdul Aziz, Siti Sumaiyah; Ibrahim, Norazila; Mohamed, Zakiah; Rajmi, Rozilah (Research Management Institute (RMI), 2023)
The effects of partial substitution of Fe at the Mn site on structural, magnetic, and electrical properties of monovalent doped Pr 0.75 Na0.05 K0.20 Mn0.95 Fe0.05 O3 manganite prepared by the solid-state method were investigated. X-ray Diffractometer, AC Susceptibility, and four point probe measurements were used to characterize the structural, magnetic, and electrical properties. The sample crystallized in an orthorhombic structure with a Pnma space group. The sample exhibited ferromagnetic (FM) to paramagnetic (PM) transition behaviour with Curie Temperature, T C value of 121.5 K. From the resistivity versus temperature analysis, the sample exhibited insulating behaviour over entire temperature from 30 K - 300 K. Fe substitution exhibited high magnetoresistance (MR %) value at low temperature region, indicating the extrinsic mechanism of MR effect.